16+2=-3(3x-6)

Simple and best practice solution for 16+2=-3(3x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16+2=-3(3x-6) equation:



16+2=-3(3x-6)
We move all terms to the left:
16+2-(-3(3x-6))=0
We add all the numbers together, and all the variables
-(-3(3x-6))+18=0
We calculate terms in parentheses: -(-3(3x-6)), so:
-3(3x-6)
We multiply parentheses
-9x+18
Back to the equation:
-(-9x+18)
We get rid of parentheses
9x-18+18=0
We add all the numbers together, and all the variables
9x=0
x=0/9
x=0

See similar equations:

| 11x+1+16x+1=18x+11 | | -6*2+k=-20 | | -0.3z=-0.93 | | 3p=4p+7 | | 15a-10=-3(-5a+2) | | 3a+11=7a-13 | | -4=a/3-6 | | 1=4c+3 | | (5x+28)=(4x+31) | | 7e+3.3=6 | | -2(5-b)+2b=-6 | | 6x+2=4x–8 | | 2)/2=6(x+3)/12 | | 5x-8=3x+2 | | 10x/7=5 | | x+1+19=4x-7 | | 8(7x+3)-5x=75 | | V-6v=-20 | | 19/n-9=6/5 | | -3x-100=-10x+30 | | n+0.9=3.6 | | -5h=11/3 | | 4d=-20* | | 2x+5-3x=40+8 | | 6(x-2)/2=6(x+3)/2 | | 1.4x+5.3x-4=2-1.12x | | 10=6+4r-5r | | 34x+180=90 | | 6n-4=-7n-4 | | -3(p+3)-5=-14-3p | | 20+4=-4(4x-6) | | -46+23=46t+23 |

Equations solver categories